Developing an MFC-based system for sludge electro-dewatering - Lim, Yiling. (2011)
Microbial fuel cells (MFC) are capable of removing organic pollutants and producing electricity simultaneously, and now holds a promising future in wastewater treatment. However, several problems such as low power output and high material costs have hindered the up-scaling of MFCs. This study targets these challenges by comparing the power generation of both granular activated carbon (GAC) dual-chamber MFC and carbon cloth single-chamber MFC. When conducting the study on GAC dual-chamber MFC, two sizes of GAC, larger GAC (LGAC) and smaller GAC (SGAC) were employed to determine the performance of different GAC size, while modifications were made to the air-cathode carbon cloth single-chamber MFC. In the single-chamber MFC, a maximum power density of 525 mW/m2 was obtained when applying the base carbon layer on different sides of the carbon cloth. Such results imply that the restriction of system could be due to other factors such as anodic performance, solution resistance instead of cathode performance. In the study of power generation using GAC dual-chamber, LGAC produced a higher power generation of 111 mW/m2, which was 3 times as much as the reactor using SGAC. Though the smaller granules provided a larger specific area for bacteria attachment, the large packing density resulted in low interstitial acetate, and hence bacterial growth could only occur at the edges. Despite continuous modifications to MFC designs, there have been limited improvements to power output and hence faces difficulties for up-scaling purposes. Hence, this FYP proposes to focus on innovative bioelectrochemical systems through the integration of MFC with sludge electro-dewatering technology instead of producing low-value electricity which could also be produced by other methods, and also discusses the capability and areas of development for such integration.